La sagesse locale de Java central dans les bandes dessinées « Bienvenue chez nous ! » et « Voilà notre tradition » - Thalia Rafifa; Sri Handayani (Universitas Negeri Semarang, 2026)
Using interesting learning media can increase students’ interest in learning about differences in intercultural understanding. Comics are an interesting learning medium because they have 2 interdependent aspects: images and language. In language learning, the use of comics is considered efficient because it can double vocabulary gains and can also arouse students’ interest in learning foreign languages (Johana & Ari, 2017). The purpose of this study is to describe the forms of local wisdom that appear in comics, through pictures or sentences, and to describe the interpretation of local wisdom based on Paul Ricoeur’s hermeneutic interpretation theory. This research uses a descriptive qualitative research method with Paul Ricoeur’s hermeneutics to analyze the symbols and meanings of the comics “Bienvenue Chez Nous !” and “Voilà Notre Tradition”. The results show that these comics present 21 local wisdoms from Central Java, organized into 11 forms and illustrated with pictures and sentences.